Mode of action of abatacept in rheumatoid arthritis patients having failed tumour necrosis factor blockade: a histological, gene expression and dynamic magnetic resonance imaging pilot study. Issue 7 (4th September 2008) - Buch, M H; Boyle, D L; Rosengren, S; Saleem, B; Reece, R J; Rhodes, L A; Radjenovic, A; English, A; Tang, H; Vratsanos, G; O'Connor, P; Firestein, G S; et al.
Abstract : Objectives: Abatacept is the only agent currently approved to treat rheumatoid arthritis (RA) that targets the co-stimulatory signal required for full T-cell activation. No studies have been conducted on its effect on the synovium, the primary site of pathology. The aim of this study was to determine the synovial effect of abatacept in patients with RA and an inadequate response to tumour necrosis factor alpha (TNFα) blocking therapy. Methods: This first mechanistic study incorporated both dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) and arthroscopy-acquired synovial biopsies before and 16 weeks after therapy, providing tissue for immunohistochemistry and quantitative real-time PCR analyses. Results: Sixteen patients (13 women) were studied; all had previously failed TNFα-blocking therapy. Fifteen patients completed the study. Synovial biopsies showed a small reduction in cellular content, which was significant only for B cells. The quantitative PCR showed a reduction in expression for most inflammatory genes (Wald statistic of p<0.01 indicating a significant treatment effect), with particular reduction in IFNγ of −52% (95% CI −73 to −15, p<0.05); this correlated well with MRI improvements. In addition, favourable changes in the osteoprotegerin and receptor activator of nuclear factor kappa B levels were noted. DCE–MRI showed a reduction of 15–40% in MRI parameters. Conclusion: These results indicate that abatacept reduces the inflammatory status of the synovium without disrupting cellular homeostasis. The reductions in gene expression influence bone positively and suggest a basis for the recently demonstrated radiological improvements that have been seen with abatacept treatment in patients with RA.